The Impact of Using a Multidimensional Teacher Evaluation System on Increasing Teacher Professional Growth - Chakerian, Taline (Technium Social Sciences Journal, 2022)
The aim of this article is to inspect the perceptions of administrators and teachers regarding the multiple data sources used to evaluate teachers, and to find out which source maximises teacher’s professional growth as perceived by administrators and teachers provided by the Armenian High schools in Beirut in Lebanon. Both quantitative and qualitative data were gathered from seven Armenian High schools in Lebanon. The quantitative data was gathered through Teacher Evaluation Profile (TEP), where N=10 administrators and N=50 teachers participated in filling out the questionnaire while the qualitative data was gathered through interview questions, where N=7 administrators and N=14 teachers participated in the interviews. The results of the study convey the importance of using multidimensional evaluation to be able to gather a wholistic view about teacher’s performance, as well as to maximise the teacher’s professional growth. However, there are also other factors and procedures that are needed to be followed.